The Legal Aspect of Registration of Different Religious Marriage Based on Determination District Court - Habib Adjie (LEGAL BRIEF, 2021)
Article 2 Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage, that pa marriage is declared valid if it is carried out according to the law of each religion and belief. However, it turned out that there were marriages that were carried out by couples of different religions based on a District Court Decision, which ordered the Population and Civil Registry Service to record the marriage. If it remains consistent that the Marriage Law does not provide opportunities for those of different religions, it turns out that there is a district court ruling that allows it. If a marriage with different religions is declared invalid, it will result in the position of the biological child on the inheritance of parents who are married to different religions, children born from a different religious marriage are children outside of marriage, because interfaith marriages are null and void and are considered never there is a marriage.